Answer: The third option
y = -6 + 2√6 ÷ 5 <em>and </em>y = -6 - 2√6 ÷ 5
Plz mark brainliest:)
Answer:
(x + 2) + x + (x + 4) = 2 (one-half x) + 2 (x + 3)
Step-by-step explanation:
triangle base: x + 2, height x, and side length x + 4 - - - -
b = x + 2 ; a = x ; c = x + 4
Perimeter (P) of a triangle :
P = a + b + c
P =( x + 2) + x + (x + 4) - (1)
Length of x + 3 with Width one haf X.
l = x + 3 w = 1/2 x
Perimeter of rectangle (P) = 2(l+w)
P = 2 ( x + 3 ) + 2 ( 1/2 x )
( Anwer)
(1) = (2)
(x + 2) + x + (x + 4) = 2(x+3) + 2(1/2x)
<u>Hope it helps!</u>